Lipid content and fatty acid profile of commonly consumed freshwater and marine fish of Bangladesh - Mohammad Shoeb; Md. Mazharul Islam; Khandoker Tahmina Tasnim; Sunjida Akter; Md. Iqbal Rouf Mamun (Current Research on Bioscences and Biotechnology, 2022)
The objectives of this research were to determine total lipid content and corresponding fatty acid profiles in freshwater (n=10) and marine fish (n=11) samples commonly consumed in Bangladesh. Lipid was extracted by Solid Phase Dispersion method. Saponification and esterification were carried out by the association of official analytical chemists (AOAC) reference procedure with some simple modifications. The fatty acids were analyzed as their methyl ester by gas chromatography equipped with flame ionization detector (GC-FID) by comparing the retention time of 13 standard methyl ester of fatty acids. Total lipid content was 0.97-8.05% and 0.97-4.33% in freshwater and marine fish, respectively. Unsaturated fatty acid in freshwater fish was found in highest amount than saturated fatty acid. Among unsaturated fatty acids, palmitoleic acid was found in highest concentration and ranged from 46.80-26.02%. Palmitic acid was found in highest amount among saturated fatty acids and ranged from 3.96-13.91%. Among the marine fishes unsaturated fatty acids (MUFAs and PUFAs) i.e; palmitoleic acid (26.21-41.61%), oleic acid (2.35-29.63%) and linoleic acid (1.40-14.45%) were predominant. Among the saturated fatty acids myristic acid (0.97-9.08%), palmitic acid (1.61-11.35%) and stearic acid (1.03-21.53%) were found to be predominant.